Acoustic analysis of speech of children - Kushalraj P (Journal of All India Institute of Speech and Hearing, 1970)
The acoustic analysis to study the speech development in children has been found to be useful, as such studies, reflect : (1) the adjustment of phonatory apparatus,(2) the shaping of the vocal tract and (3) the timing and co-ordination of articulation and thus provide evidence regarding the anatomical and neuromuscular maturation of speech mechanism. This information has been found to be useful in early identification diagnosis and treatment of various speech and language disorders.